Physicochemical and Sensory Properties of Instant Perkedel using Kluwih Seed Flour and Potato Flour - Intan Kusumaningrum; Distya Riski Hapsari; Putri Nurul Fauziah (JURNAL AGROINDUSTRI HALAL, 2021)
This research were aimed to study the effects of the kluwih seed flour and potato flour combination on the sensory properties of instant perkedel and the physicochemical properties of the selected product. This study used a factorial Completely Randomized Design (CRD) with one factor. The factor was combination of kluwih seed flour and potato flour with 5 treatment levels A1 (20%:80%), A2 (25%:75%), A3 (50%:50%), A4 (75%:25%) and A5 (100%:0%). Data were analyzed by ANOVA with Duncan’s Advance Test. Selected perkedel was A3 treatment with the highest sensory and hedonic value. The selected product had the properties sensory of color lead to white bone (8.0), aroma lead to not typical kluwih (6.5), taste lead to not bitter (8.4), and texture lead to compact (8.1). The value of the hedonic result indicated preference for color 7.9, aroma 7.5, taste 7.5, texture 8.0 and overall 6.9. Physical analysis result showed there was no significant difference between the selected and the control one with brightness value 58.57. Meanwhile, the hardness of the selected product is harder than the control with hardness value 3915.5 gf. The results of the chemical analysis of the selected product had moisture content 50.71%, ash content 2.87%, protein content 3.47%, fat content 9.08%, carbohydrate content 33.88% and dietary fiber content 6.03%. Overall the chemical test results of the selected product tend to be better than the control.